O poder e a política de Michel Foucault - Foucault, Michel (Ecopolítica, 2015)
Entrevista inédita, em português, de Michel Foucault a Peter Maas e David Brock. Publicada originalmente na edição de 22 de abril de 1983 do The Daily Californianís Weekly Magazine. ABSTRACT: Unpublished interview in portuguese with Michel Foucault by Peter Maas and David Brock. Originally published in The Daily Californians Weekly Magazine on April 22, 1983.